2020
DOI: 10.3389/fmars.2020.00125
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use Patterns and Identification of Essential Habitat for an Endangered Coastal Shark With Vertebrae Microchemistry: The Case Study of Carcharhinus porosus

Abstract: Sharks are among the most endangered and data poor vertebrates in the world. The lack of information regarding their habitat use is especially concerning since these are crucial for the establishment of priority areas for species conservation. Investigating the trace elements present in shark vertebrae has become an interesting tool to analyze species habitat use over individuals' lifetimes. Therefore, we applied vertebrae microchemistry to investigate habitat use of Carcharhinus porosus in Brazil's Northern C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Recent data using vertebrae microchemistry has demonstrated that the BNC might actually be an essential habitat, especially for species that fulfill their entire life cycle in the area [ 40 ]. Indeed, habitat use data indicate that C .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent data using vertebrae microchemistry has demonstrated that the BNC might actually be an essential habitat, especially for species that fulfill their entire life cycle in the area [ 40 ]. Indeed, habitat use data indicate that C .…”
Section: Discussionmentioning
confidence: 99%
“…porosus is much more vulnerable to the fishing activity than other migrating coastal species such as Galeocerdo cuvier [ 90 ]. Despite this, species distribution modelling and historical catch data estimated that the Amazon coast is the area where the species has the highest catch and occurrence probability throughout its distribution range [ 40 ]. Therefore, the Amazon coast is likely the most important area for this species throughout its distribution, but is also where fisheries exposure are likely the highest [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations